2015
DOI: 10.1074/jbc.c114.627778
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacological Inhibition of ULK1 Kinase Blocks Mammalian Target of Rapamycin (mTOR)-dependent Autophagy

Abstract: Background: Autophagy is an intracellular lysosomal degradation pathway implicated in many diseases, but there are currently no specific autophagy inhibitors.Results: Small molecule inhibition of ULK1, the upstream autophagy initiating kinase, blocks autophagosome initiation and maturation.Conclusion: ULK1 plays a role in autophagosome maturation as well as initiation.Significance: ULK1 can be targeted to block autophagy for disease therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
198
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(212 citation statements)
references
References 47 publications
12
198
1
1
Order By: Relevance
“…In parallel, increasing attention has been dedicated to components of the autophagic machinery that seem to have limited roles in other processes, such as autophagy-related 4B cysteine peptidase (ATG4B; which can be targeted by NSC185058) 297 and UNC-51-like autophagy-activating kinase 1 (ULK1; which can be targeted by SBI-0206965, MRT67307 and MRT68921) 298,299 , as well as to specific autophagic pathways, including mitophagy and LC3-associated phagocytocis (LAP) 193,213 . Lys05, SAR405, NSC185058, and SBI-0206965 have been shown to mediate anticancer effects in vitro and in vivo 294,295,297 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, increasing attention has been dedicated to components of the autophagic machinery that seem to have limited roles in other processes, such as autophagy-related 4B cysteine peptidase (ATG4B; which can be targeted by NSC185058) 297 and UNC-51-like autophagy-activating kinase 1 (ULK1; which can be targeted by SBI-0206965, MRT67307 and MRT68921) 298,299 , as well as to specific autophagic pathways, including mitophagy and LC3-associated phagocytocis (LAP) 193,213 . Lys05, SAR405, NSC185058, and SBI-0206965 have been shown to mediate anticancer effects in vitro and in vivo 294,295,297 .…”
Section: Figurementioning
confidence: 99%
“…SAR405 and SBI-0206965 synergized with mTORC1 inhibitors in arresting the proliferation of human lung (H1299 and A549) and kidney (ACHN and 786-O) cells in vitro 295,298 . Conversely, the potential therapeutic activity of VPS34-IN1 (which has been characterized biochemically in human osteosarcoma U2OS cells), MRT67307 and MRT68921 (both of which have been studied for their biochemical properties in mouse embryonic fibroblasts) has not yet been tested in relevant disease models 296,299 . Thus, the actual therapeutic potential of these approaches remains largely unexplored.…”
Section: Figurementioning
confidence: 99%
“…When mTORC1 is active, it inhibits autophagy by phosphorylating both ULK1 and ATG13 (Table 1), reducing ULK1 kinase activity [1113,22,23]. Chemical inhibition of ULK1 prevents rapamycin from triggering autophagy, demonstrating that regulation of ULK1 is a key step in autophagy induction downstream of mTORC1 inhibition [24]. When mTORC1 is inhibited under starvation conditions, it dissociates from ULK1 [12].…”
Section: Upstream Regulation Of the Ulk1 Complexmentioning
confidence: 99%
“…The past year saw several reports of ULK1 inhibitors [24,37,40,41]. Petherick et al describe the compounds MRT67307 and MRT68921, and used them to conclude that ULK1 kinase activity is important in autophagosome maturation as well as initiation.…”
Section: Substrates and Inhibitors Of The Ulk1 Complexmentioning
confidence: 99%
“…To confirm the involvement of the AMPK-ULK1 pathway in 6-OHDA-induced autophagy and PARK7 secretion, SH-SY5Y cells were treated with MRT68921, a specific inhibitor of ULK1 [47], as a result of which it was found that 6-OHDA-induced increase in LC3B-II levels was suppressed by co-treatment with MRT68921 (Figure 7(D)). Furthermore, 6-OHDA-induced PARK7 secretion was suppressed by co-treatment with MRT68921 (Figure 7(E)).…”
Section: Resultsmentioning
confidence: 99%